Professional learning of pharmaceutical care in a virtual world - Ana MARTÍN SUÁREZ; Diego SÁNCHEZ VICENTE; Juan Francisco MARTÍN IZARD; Emilio CLAVIJO COBALEDA (Ediciones Universidad de Salamanca, 2011)
<!--[if gte mso 9]> 0 0 1 141 776 Instituto Universitario de Ciencias de la Educación 6 1 916 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES JA X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="64" SemiHidden="false" UnhideWhenUsed="false" Name="Medium Shading 2 Accent